The Importance of a Child's Brain Development in Mental Arithmetics and its Role in Life - Sharora Khamrayeva Rustambek qizi (Zien Journals, 2022)
This article discusses mental arithmetic in preschool education and provides a promising platform for further education, allowing to achieve excellent intellectual and creative development results in the learning process.
Keywords: Mental arithmetic; mathematics; ability; memory